Ao vivo em São Paulo: a produção de sentidos nas transmissões dos ataques do PCC - Albani, João Gabriel (2007)
This research examines the production of meanings of the broadcasted transmissions in open TV news programs on the 15th of may, 2005, when the Primeiro Comando da Capital attacks occurred in São Paulo. In the present days television, especially on news programs, applies the broadcast, particularly the live transmition. There s relevancy in investigating how the broadcast is fundamental on establishing a strong communicational contract between enunciator and enunciatee. For the corpus we selected from TV Globo the news extra bulletings SPTV and Globo Notícias, the news programs Jornal Nacional and SPTV 1ª Edição, and SBT`s São Paulo Contra o Crime special edition program as well as their news extra bulletins. From the speech theories and the audiovisual analysys methodology (Arlindo Machado, Beatriz Becker, Yvana Fechine de Brito, Nilton Hernandes e Valdério de Almeida), we performed a detailed examination of the programs in the corpus, studying the effects of meaning produced in the real time informative audiovisual texts. In the examined corpus, the effort to the passionalization of fear seemed to become, as the work s hypothesis, one essential resource used in the constitution of the communicational contract between enunciator and enunciatee, intimately connecting itself to the broadcast resource. There were highlighted effects of meaning of fear, insecurity, simultaneousness and ubiquity, we identified as well the course of passionlalization of fear. We emphasize the parcial approach of television companies on the news coverage about the consequences of the PCC attacks; their goal was to use live broadcast transmissions to enrapture the viewers attention, disregarding the television`s importance as Brazil s most efficient information broadcaster. Still we identified the TV`s attempt to transform the violent broadcasted events in a great media event, which would involve the whole society, initiated by criminals, but then turned into a nation integrator thanks to the TV channels efforts